The Psychic Explorer - Cainer, Jonathan; Rider; Carl (London Guild Publishing, 1986)
A lively, authoritative introduction to six popular magical arts--astrology, auras, the Tarot, dowsing, palmistry, and ESP, this attractively illustrated book helps readers uncover their own inner powers of psychic awareness and develop their divination skills.
Include Bibliography and Index.
A Practical Guide to Modern Magic.
Keywords: Occultism -- Parapsychology